Deployed model of extremal system operation for solving optimal management problems - Lutsenko, Igor (Eastern-European Journal of Enterprise Technologies, 2014)
The reduced, simplified registration mathematical model of the system operation, obtained by scaling the registration signals of the basic model and determining the sum of the reduced, integrated flow rates by the input and output of the system under study was constructed. The studies of this traditional, for today model have shown the problem, associated with the existing approach in operations identification. As a result of using the agent model and system approach, it was found that registration model of the operation is not based on the data, actually describing the process under investigation. The new idea of the studied process has allowed to develop a method for constructing the reduced, deployed model of the operation. The deployed model of the operation allows to get access to data of operations at each point of the model of the operation process. The developed approach to constructing the mathematical model of the reduced deployed operation allows more accurate identification of the operation and its use to obtain new scientific results in the field of operations research.